The Authority of the Governor Regarding Termination of Members of the Regional People's Legislative Assembly in the Perspective of State Administration in Indonesia - Benito Asdhie Kodiyat; Cynthia Hadita (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Problems with the interim dismissal of members of the regional people's representative council who are related to the authority of the governor. The research method used is normative juridical with library research. The results of the study show that within 7 (seven) days of receiving the proposal to dismiss a member of the Regency/Municipal DPRD, it is obligatory to submit the proposal to the Governor. If within 7 (seven) days the regent does not submit a proposal to dismiss a member of the Regency/Municipal DPRD, the leadership of the Regency/Municipal DPRD will immediately submit the proposal to the Governor and within 14 (fourteen) days, the Governor must formalize the dismissal of the member of the Regency/Municipal DPRD